Moral migration and transnationalism: Russian anti-war resistance after the full-scale invasion of Ukraine - Oula Kadhum (Comparative Migration Studies)
Abstract This paper examines the role of morality in migration and transnationalism, focussing on the case of Russian anti-war migration and activism against the full-scale invasion of Ukraine and Putin’s regime. Drawing on moral philosophy and psychology, I argue that Russian departure and activism can be conceptualised as moral migration and transnationalism, defined as “decisions, reasoning, judgements and acts of resistance motivated by obligatory concerns for others’ welfare, rights, fairness and justice”. Applying this to Russian anti-war activism abroad, the paper underlines how the act of migration can be conceptualised as a form of moral protest, especially for citizens from authoritarian states and autocratic regimes. It also emphasises the role of morality in transnational mobilisation choices and causes activists take up, as well as the moral dilemmas and controversies these present for anti-war communities and movements. By foregrounding the significance of morality, this study seeks to redress its neglect in migration and transnationalism scholarship and underscores the importance of moral theory in the analysis of international politics. Additionally, the paper introduces a new case study of anti-war activism and mobilisation among Russia’s emergent anti-war migrant communities in London, Madrid, and Tbilisi, thereby illuminating a critical yet under-researched dimension of the geopolitics of Russian opposition movements.